A DISCUSSION OF INTELLECTUAL HISTORY, JURISPRUDENTIAL THEORIES AND FEMINISM IN THE ERADICATION OF EPISTEMIC VIOLENCE IN SOUTH AFRICA (The Pretoria Student Law Review, 2021)
This analysis and discussion of intellectual history, along with analysing theories concerned with legal pluralism, provides insight into the ideas and ideologies currently influencing jurisprudence that aims to eradicate epistemic violence. This paper will illustrate how the aforementioned analysis, along with the concept of transformative constitutionalism, actively contributes towards the development of jurisprudence that aims to diminish epistemic violence and the inequality that emanates from it. The paper will illustrate how theories concerned with legal pluralism, traditions and ideologies, such as Marxism, Black Consciousness, feminism and religion, all play a role in contributing towards the development of a critical jurisprudence that will aim to eradicate epistemic violence in several sectors of the South African society. This paper will further illustrate how feminism as an ideology, and in the field of sociological law, can uncover and subsequently empower hidden and marginalised narratives, thereby promote the eradication of epistemic violence. In addition, the paper will include an analysis of a feminist poem by a South African feminist scholar to highlight the relevance of the ideology of feminism in combatting epistemic violence.
Keywords: intellectual history; eradicate epistemic violence; transformative constitutionalism; feminism